Dual-band dual-sense circularly polarized U- and L-shaped strip monopole antenna for WiMAX/WLAN applications. Issue 18 (12th December 2019) - Bag, Biplab; Biswas, Priyabrata; Mondal, Rahul; Biswas, Sushanta; Sarkar, Partha Pratim
Abstract : In this paper, a single-layer dual-band dual-sense circularly polarized monopole antenna is presented for Wireless Local Area Network (WLAN) and Worldwide Interoperability for Microwave Access (WiMAX) applications. The proposed antenna consists L, U shape strips and a 50 Ω microstrip feedline. This antenna is printed on one side of low-cost FR4 epoxy substrate with a thickness of 1.6 mm and partial ground plane is on the other side of the substrate. The overall dimension of the substrate is 0.417 λ 0  × 0.292 λ 0  × 0.0133 λ 0 . The antenna may operate in two bands: the lower band is from 2.35 to 3.22 GHz, centred at 2.52 GHz (percentage bandwidth od 34.52%) and the upper band is from 4.78 to 5.79 GHz, centred at 5.49 GHz (percentage bandwidth of 18.39%). In addition, 3 dB axial ratio bandwidth of the lower and upper bands are 650 and 650 MHz, respectively. The detailed performances of the proposed antenna are demonstrated along with the measured and simulated results.